Logro de competencias investigativas en estudiantes universitarios peruanos de ciencias médicas: una experiencia a través del uso del aula invertida - Cardoza Sernaqué, Manuel Antonio (2022)
Conferencia de la 20th LACCEI International Multi-Conference for Engineering, Education, and Technology: “Education, Research and Leadership in Post-pandemic Engineering: Resilient, Inclusive and Sustainable Actions”. hybrid event, Boca Raton, Florida- USA, junio 18 - 22.